Challenges and possibilities in the inclusion of students with ASD in Physical Education classes (Research, Society and Development, 2022)
This paper aims to present qualitative bibliographic research where we address school inclusion, more precisely of students in Autism Spectrum Disorder (ASD) in physical education classes. The research is made by using books related to the topic being used as the main source, as well as articles published on Google academic platforms from the years 2015 to 2022. Considering that currently we can see that much has been said about inclusion, which can be understood in many ways, in view of the growing demand of students with ASD joining regular schools and the concern of professionals who often do not feel prepared to develop their practices. This research has the general objective of informing and assisting these professionals in the inclusion of students with ASD in class. The data were analyzed based on Bardin's content analysis. It is intended that with the presentation of these topics there is a greater clarification on the part of the professionals involved in the learning of students with ASD and that they realize that inclusion is possible as long as the re-signification of their practices takes place.